The thoughts of Imam Ash-shafi’ie on interpersonal skills in self development: a conceptual analysis - Wan Zulkifli Wan Hassan; Khalim Zainal; Nazri Muslim; Nik Yusri Musa; Azizi Umar; Jamsari Alias; Azwira Abdul Aziz; Hasnan Kasan (2013)
Interpersonal skill refers to an algorithm of mental and communication adopted in social and communication interaction in achieving specific impact and decision. Fundamental concepts of interpersonal communication include self-independence, attitude, personality, value and goal. These attributes undeniably help create an individual capable of interacting confidently with his surroundings which is a prerequisite for the development of a civilized society. One prominent figure who contributed significantly to this field was Imam ash-Shafi'ie. Even though Imam ash-Shafi'ie is well known in the Muslim world as a notable legal scholar, this article attempts to expose his valuable thoughts and contributions to this field which acclaimed him as one of the reformist in the field of self development.